Systems Approaches to Occupational Vocal Health: Considerations for Community Faith Leaders - Buckley, Katie L. (Journal of religion and health, 2022)
Systems thinking approaches can benefit the occupational vocal health of vocally reliant workers. This paper explores community faith leaders as an example of a highly vocally reliant occupation, who may benefit from systems thinking being used to support their vocal occupational health and safety. A scoping review of the current literature regarding faith leaders’ occupational voice use and vocal health is detailed, including recognised occupational hazards. This article then discusses the unique and potential use of systems thinking for facilitating faith leaders’ vocal occupational health and safety. Rather than using a solely clinical perspective, the sociotechnical systems approach and the biopsychosocial-spiritual approach are noted as particularly pertinent for this occupational group.